(untitled) (Journal of Informatics Education and Research, 2024)
Tourism, a burgeoning global industry, relies heavily on effective destination branding. Factors such as natural beauty, adventure, cultural heritage, and religious significance contribute to a destination’s popularity. To understand the process of building a successful destination brand, this study explores key dimensions: awareness, image, experience, identity, and meaning. Through a systematic literature review, the researchers propose a model illustrating the interrelationships between these dimensions. By creating consumer-based brand equity, destinations can attract tourists and drive economic growth.